Effects of DDT on Steroid Metabolism and Energetics in Bobwhite Quail (Colinus Virginianus) - Sheldon Lustick; Terry Voss; Tony J. Peterle (National Quail Symposium Proceedings, 2017)
Female bobwhite quail (Colinus virginianus) fed low levels (5 ppm) of DDT in their diets showed increased enzyme induction in the liver and consequently a significant increase in steroid (progesterone) metabolism (a mean of 54% conversion of progesterone to its more polar metabolite in experimentals compared to a mean of 24.1% conversion in controls). The mean conversion of testosterone to its polar metabolite (25.1%) in experimental males was greater than in the controls (mean 18.1%) but was only significantly greater in certain males. There was a correlation (r = 0.7 P<0.01) between percent body weight of testes and percent conversion of testosterone to its metabolites (the smaller the testes the greater the conversion). A correlation (r = 0.66 P<0.02) was also found between circulating levels of DDE, DDT, and testes size (the higher the pesticide level the smaller the testes). Dietary levels of DDT (10,50,100,150 ppm) affected the energetics (oxygen consumption) of bobwhite quail. All DDT-treated birds had a higher metabolic rate than the controls at all ambient temperatures tested except 30 C. After acclimation to an ambient temperature of 5 C for 10-13 weeks, birds on 100-ppm DDT diets had a significantly (P<0.01) higher metabolic rate than controls. After one week of exposure to -18 C there was a significant (P<0.02) increase in thyroid weight in the birds on 100-ppm diets. Birds on 100-ppm diet exposed to extreme cold for 1 week died of DDT toxicity. Data on tissue residue levels, weight changes, I uptake by the thyroid, and adrenal changes are also presented. The ecological significance of the synergistic effect of DDT and cold stress on the bobwhite quail is discussed.